TINDAK PIDANA PENIPUAN PADA TRANSAKSI E-COMMERCE DI MASA PANDEMI COVID-19 - Rosalia Dika Agustani; Ahmad Nur Setiawan (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
There are many businesses that divert their business using e-commerce media. E-commerce media is intended to be a digital platform that can directly connect between businesses and consumers without having to face-to-face. In the business world, the proliferation of e-commerce does lead to rapid economic growth. But the number of transactions through e-commerce also acts to close the possibility of criminal acts of online fraud and in this case the victims are consumers. This research uses juridical-normative methods, with a legal approach, conceptual approach, and case approach. Consumers who experience criminal acts of online fraud can take legal action as the first is to make a complaint to law enforcement, the complaint must attach evidence and can convince that he/she has been victimized. So that law enforcement can take the next step that will usually be searched for the identity of the business. The role of digital proofing greatly influences the results of investigations. Not all online crimes can be solved due to limited law enforcement capabilities. So that the accountability of business actors has been explained in Article 28 paragraph (1) jo. Article 45 paragraph (2) of the ITE Act.